Myocardiopericarditis in adult Still's disease - Horna, Manuel (2020)
Cardiac involvement in Adult-onset Still’s Disease (AOSD) usually manifests as a pericardial disease, that has a benign course. The myocarditis is a rare complication with 7% of prevalence. The diagnosis of AOSD is based in the Yamaguchi or Fautrel criteria. The treatment with steroids, metrotexate is the first and second therapeutic lines, respectively, the combination is effective in 70% of cases. We report one case of AOSD with unusual presentation of double cardiac commitment, Myopericarditis.